Field evaluation of specificity and sensitivity of a standard SARS-CoV-2 antigen rapid diagnostic test: A prospective study at a teaching hospital in Northern Ghana. - Alhassan Abdul-Mumin; Abdulai Abubakari; Faith Agbozo; Abass Abdul-Karim; Benjamin Demah Nuertey; Kareem Mumuni; Anna-Katharina Heuschen; Lisa Hennig; Claudia M Denkinger; Olaf Müller; Albrecht Jahn (PLOS Global Public Health, 2021)
The testing capacity for SARS-CoV-2 in Africa is rather limited. Antigen detection rapid diagnostic tests (Ag-RDTs) are a cheap and rapid alternative to reverse transcriptase-polymerase chain reaction (RT-PCR) tests, but there is little data about their performance under real life conditions in tropical countries. The objective of this study is to evaluate the performance of a standard Ag-RDT in a population of a major hospital in northern Ghana. Prospective, cross-sectional, blinded verification of the performance of the SD Biosensor Standard Q SARS-CoV-2 Ag-RDT under real life conditions in 135 symptomatic patients and 58 contacts of RT-PCR positives at Tamale Teaching Hospital in February 2021. Nasopharyngeal samples were taken under standard conditions and tested against RT-PCR in the hospital laboratory. 193 participants (median age 35 years, 109 male) were included into the study for which both RT-PCR test and Ag-RDT results were available. A total of 42 (22%) were RT-PCR positive. Of the 42 RT-PCR positives, 27 were Ag-RDT positive, resulting in a sensitivity of 64% (95% CI 49-79). Sensitivity among symptomatic patients was 58% (95% CI 38-78). 123 were identified Ag-RDT negatives of the 151 RT-PCR negatives, resulting in a specificity of 81% (95% CI 75-87). SARS-CoV-2 Ag-RDTs appear to have a rather low sensitivity and particularly a low specificity under real life conditions in Africa. The role of existing Ag-RDTs in countries with high-temperature climates and limited resources still needs more data and discussion.